2021
DOI: 10.1038/s41598-021-84344-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between food insecurity and key metabolic risk factors for diet-sensitive non-communicable diseases in sub-Saharan Africa: a systematic review and meta-analysis

Abstract: In previous studies, food insecurity has been hypothesised to promote the prevalence of metabolic risk factors on the causal pathway to diet-sensitive non-communicable diseases (NCDs). This systematic review and meta-analysis aimed to determine the associations between food insecurity and key metabolic risk factors on the causal pathway to diet-sensitive NCDs and estimate the prevalence of key metabolic risk factors among the food-insecure patients in sub-Saharan Africa. This study was guided by the Centre for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 71 publications
1
19
0
Order By: Relevance
“…While the prevalence of overweight is comparable to those reported in previous studies, the rates of obesity in our study were slightly higher than those reported among women in the general population of Eswatini [ 4 ]. The high rates of overweight/obesity observed among women living with HIV in our study are alarming, particularly due to their association with increased risk of NR-NCDs [ 2 , 9 , 10 , 24 ]. Furthermore, our findings show significantly higher rates of overweight/obesity among women who perceived themselves as being in good health.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…While the prevalence of overweight is comparable to those reported in previous studies, the rates of obesity in our study were slightly higher than those reported among women in the general population of Eswatini [ 4 ]. The high rates of overweight/obesity observed among women living with HIV in our study are alarming, particularly due to their association with increased risk of NR-NCDs [ 2 , 9 , 10 , 24 ]. Furthermore, our findings show significantly higher rates of overweight/obesity among women who perceived themselves as being in good health.…”
Section: Discussionmentioning
confidence: 89%
“…Among studies in sub-Saharan Africa, household food insecurity has been adversely associated with an increased prevalence of multiple metabolic risk factors including overweight, obesity, dyslipidemia, and hypertension [ 24 ]. The impact of food insecurity on food choices, dietary intake, and nutritional status has long been recognized [ 21 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor nutrition is a major risk factor for diet-related noncommunicable diseases (NCDs) [ 8 , 9 ]. Food insecurity is associated with worsening nutrition and increased NCDs [ 10 ]. Increased frequency of extreme weather events as a result of climate change, and more recent crisis events, including the current COVID-19 pandemic, have affected food and water security [ 2 , 11 ].…”
Section: Introductionmentioning
confidence: 99%